Pengaruh Pembelajaran IPS Berbasis Budaya Terhadap Sikap Toleransi Antarbudaya Siswa Sekolah Menengah Pertama - Labibah Azzahra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to examine the influence of culture-based Social Sciences (IPS) learning on students' intercultural tolerance attitudes. The background to this research is the importance of increasing understanding and attitudes of intercultural tolerance in the context of multicultural education in Indonesia. The research method used was quasi-experimental with a pretest-posttest control group design. The research sample consisted of class VII students at one of the junior high schools in Jakarta, who were chosen randomly. The experimental group received culture-based social studies learning for one semester, while the control group received conventional learning. The research instrument was an intercultural tolerance attitude questionnaire which had been tested for validity and reliability. Data were analyzed using the t test to see the differences in pretest and posttest scores between the experimental and control groups. The results showed that there was a significant increase in intercultural tolerance attitudes in the experimental group compared to the control group. Culture-based social studies learning has proven effective in increasing students' attitudes of intercultural tolerance. These findings indicate that the integration of local cultural values ​​in the social studies curriculum can be a potential strategy for developing attitudes of intercultural tolerance and harmonization in schools. This research recommends the wider application of culture-based learning in education to support the creation of an inclusive and tolerant school environment.